Experimental study of wrinkling behavior of membrane structures via visual method. (April 2020) - Dai, Xiangjun; Yuan, Tianyu; Zu, Zheng; Shao, Xinxing; Li, Lijun; Cheng, Xiangmeng; Zhou, Jilei; Yang, Fujun; He, Xiaoyuan
Abstract: In this study wrinkling behavior of membrane structures was investigated by visual methods. A dual-biprism-based stereo camera system was employed to obtain image pairs of the membranes before and after deformation. The digital image correlation (DIC) method was used to determine the out-of-plane displacements, wrinkle amplitudes, and strain distributions of the membranes, which were subjected to different shearing loadings. Moreover, the critical wrinkle strains were calculated based on the tension field theory. To elucidate the effects of the length/width ratio on the wrinkling behavior, wrinkling experiments were performed on specimens with four different length/width ratios but the same thickness. In addition, the surface and internal in-plane stresses of the structures were determined by both three-dimensional DIC and the digital gradient sensing method. The results indicated that a stress-change occurs between the membrane surface and its inner structure. Finally, the critical shear displacements determined using the two methods were found to be very close. Highlights: We propose visual methods for studying wrinkling in membranes. Dual-biprism stereo camera is used to record images before/after deformation. Digital image correlation is used to calculate parameters of wrinkled membrane. Specimens with varying length/ratios were subjected to shear displacements. Results suggest stress is transferred between surface and inner structure.